Abstract

No abstract available.

• View by:
• |
• |
• |

Cited By

OSA participates in Crossref's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Fig. 1
Fig. 2
Fig. 3
Fig. 4
Fig. 5
Fig. 6

Equations (22)

$S x = W x - W 0$
$W x = e c ( d x - f ) d x and W 0 = e c ( d 0 - f ) d 0 ,$
$S x = e c f ( 1 d 0 - 1 d x ) .$
$I x I x + V = M S x e ,$
$I x = V M S x e - M S x .$
$I x = e c M f V ( d x - d 0 ) e d x d 0 - e c M f ( d x - d 0 ) .$
$I x = M f V ( d x - d 0 ) d x d 0 - M f ( d x - d 0 ) .$
$y - I y X - I x = I y - d y I x - ( d x - f - N ) .$
$X = I y ( f + N ) + I x d y - I y d x d y - I y$
$Z = f d y d x$
$Z = I y V M ( I x + V ) .$
$d y = I y V d x M f ( I x + V ) .$
$X = M f d 0 [ N - ( V - f ) ] ( d 0 - M f ) d x + M f ( V - d 0 ) d 0 - M f .$
$X = M f ( V - d 0 ) d 0 - M f .$
$M f ( V - d 0 ) d 0 - M f .$
$I ∞ = V M f d 0 - M f ,$
$I ∞ C = V M f d 0 - M f - M f ( V - d 0 ) d 0 - M f$
$C y = M f d 0 d 0 - M f .$
$C x = V M f d 0 - M f .$
$C y = M f d 1 d 1 - M f$
$C x = V M f d 1 - M f .$
$d 1 = M f = V or e d 0 e 1 = M f = V .$